The Influence of Digital Content Marketing and Consumer Engagement on Online Purchasing Decisions through Shopee - Annida Fatihatul; Abdul Muizz Wadud; Refaldo Fanther (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
This research was conducted to determine the influence of digital content marketing and consumer engagement on online purchasing decisions through Shopee. The increasingly rapid technology in this modern era has caused a shift in human behavior, especially when it comes to shopping. Regarding online shopping, many factors can influence this shopping activity or what is usually called consumer behavior. Various marketplaces such as Shopee are starting to offer various conveniences to meet people's needs by shopping online. This research uses qualitative methods with the type of research being library research, which is a series of collection methods by reading books, journals, articles and previous research related to our current research. The results of this research found that digital content marketing and consumer engagement have a positive effect on online purchasing decisions through Shopee. This means that consumers feel that digital content marketing and consumer engagement can carry out their functions well.